1995
DOI: 10.1093/oxfordjournals.humrep.a135915
|View full text |Cite
|
Sign up to set email alerts
|

Minor congenital anomalies, major congenital malformations and development in children conceived from cryopreserved embryos

Abstract: A total of 91 children (68 singletons, 20 twins and three triplets) who were conceived from cryopreserved embryos between 27 December 1989 and 18 January 1994, and 83 normally conceived control children (81 singletons and two twins) of a similar age, sex and social class, were assessed for minor congenital anomalies and major congenital malformations. Their development was assessed using the Griffiths Scales of Mental Development. The incidence of minor congenital anomalies (31.9% in the cryopreserved embryo g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(37 citation statements)
references
References 0 publications
1
33
2
1
Order By: Relevance
“…Our findings are reassuring and in line with the recent studies in young IVF children [2,4,7,8,10,11,14,[19][20][21][22][23][24][25] and at primary school age [12,17,18]. Olivennes et al [17] found, in a follow-up study of 422 IVF children aged 6 to 13 years, according to the French school system, that 92.2% of the children had at least average school achievement.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are reassuring and in line with the recent studies in young IVF children [2,4,7,8,10,11,14,[19][20][21][22][23][24][25] and at primary school age [12,17,18]. Olivennes et al [17] found, in a follow-up study of 422 IVF children aged 6 to 13 years, according to the French school system, that 92.2% of the children had at least average school achievement.…”
Section: Discussionsupporting
confidence: 90%
“…From the psychological point of view, mental and psychomotor development in the early years was an important focus. Although IVF pregnancies appear to be associated with an increased risk of multiple pregnancy, preterm delivery, low birth weight, [2,7,8,10,14,16,[21][22][23][24][25]. Developmental and neurological problems that were found at this young age were mainly related to prematurity, low birth weight, or multiple births [2,3,15].…”
Section: Introductionmentioning
confidence: 99%
“…Other older studies with less methodological consistency also report similar findings. 15,18,19,26,31 Comparison of the birth defect studies is confounded by differences in the definitions used to classify the birth defects, in the reporting of congenital abnormalities, and in the methods used for statistical analysis. These caveats present challenges for interpretation of this data.…”
Section: Congenital Disorders And/or Hormonal Abnormalities In Offsprmentioning
confidence: 99%
“…The details of the meta-analysis-including the literature search, the study selection and the data extraction processes-are described there. We found 19 studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] for inclusion in the meta-analysis and found that ART increased the risk of MM with an odds ratio of 1.29 (95% CI 1.01-1.67). Our major conclusion was that the risk we found may be inflated by the fact that none of the studies used the most appropriate control group, namely subfertile couples conceiving spontaneously.…”
Section: Introductionmentioning
confidence: 99%